Biomechanical Functional Elbow Restoration of Acute Ulnar Collateral Ligament Tears: The Role of Internal Bracing on Gap Formation and Repair Stabilization. Issue 8 (July 2020) - Bachmaier, Samuel; Wijdicks, Coen A.; Verma, Nikhil N.; Higgins, Laurence D.; Greiner, Stefan
Background: Biomechanical studies have compared augmented primary repair with internal bracing versus reconstruction techniques of the anterior ulnar collateral ligament (aUCL) in the elbow. However, aUCL repair alone has not been compared with augmented repair or reconstruction techniques. Hypothesis: Internal bracing of aUCL repair provides improved time-zero stabilization in terms of gap formation, torsional stiffness, and residual torque compared with both repair alone and the modified docking technique, with enhanced valgus stability restoration to that of the native ligament. Study Design: Controlled laboratory study. Methods: We randomized 8 matched pairs of cadaveric elbows to undergo either augmented aUCL repair or a modified docking technique through use of the palmaris longus tendon. Valgus laxity testing was consecutively performed at 90° of flexion on the intact, torn, and repaired conditions as well as the previously assigned techniques. First, intact elbows were loaded up to 10 N·m valgus torque to evaluate time-zero ligament rotations at valgus moments of 2.5, 5.0, 7.5, and 10 N·m. Rotation controlled cycling was performed (total 1000 cycles) for each surgical condition. Gap formation, stiffness, and residual torque were analyzed. Finally, these elbows and 8 additional intact elbows underwent torque to failure testing (30 deg/min). Results: Repair alone revealed low torsional resistance and gapping, similar to the torn state. The augmented repair technique showed significantly higher torsional stiffness ( P < .001) and residual torque ( P < .001) compared with all other conditions and restored native function. Although reconstruction revealed similar initial stiffness and residual torque compared with an intact ligament, a steady decrease of torsional resistance led to a completely loose state at higher valgus rotations. Analysis of covariance between all groups showed significantly less gap formation for augmented repair ( P < .001). The native failure load and stiffness were significantly higher and were similar to those of augmented repair ( P = .766). Conclusion: Internal bracing of aUCL repair restored valgus stability to the native state with statistically improved torsional resistance, loading capability, and gap formation compared with reconstruction, especially at the upper load range of native aUCL function in the elbow. Clinical Relevance: We found that aUCL repair with an internal brace effectively improves time-zero mechanical characteristics and may provide stabilized healing with accelerated and reliable recovery without the need for a tendon graft.